Speed of Online and Print Peer-Reviewed Ophthalmology Publications and Correlation to Journal Bibliometric Measures - Nuesi, Ronaldo; Lee, John Y.; Kuriyan, Ajay E.; Sridhar, Jayanth (Journal of Academic Ophthalmology, 2020)
Objective This study aimed to explore the relationship between publishing speeds and peer-reviewed journal bibliometric measures in ophthalmology.Methods Journal Citation Reports and Scopus Database were accessed for identification of journal bibliometric measures in ophthalmology. Twelve randomly selected articles from 2018 for all identified journals were studied. All outcome measures were extracted from the full text of articles and correlated with journal bibliometric measures. Statistical analysis was performed on measured parameters in comparison to a previous study.Main Outcomes and Measures Journal impact factor, Eigenfactor score, and CiteScore were correlated with time from submission or acceptance of manuscripts to online and print publication. The correlation between study design and publishing speeds was also assessed.Results A total of 55 journals were included for a total of 657 articles. Online publications were significantly faster than print publications for almost every journal (p < 0.001). Laboratory experimental studies had significantly shorter times from submission to online publication (p = 0.002) and acceptance to online publication (p < 0.001) compared with observational and interventional studies. Journal impact factor was positively correlated to publishing speed from acceptance to online publication (p = 0.034). CiteScore was positively correlated to speed from submission to print publication (p = 0.04), acceptance to print publication (p = 0.013), and acceptance to online publication (p = 0.003). Eigenfactor score was not statistically significant when correlated with any outcome measures.Conclusion Online publication has increased speed of dissemination of knowledge in the ophthalmology literature. Despite reporting higher numbers of submissions every year, ophthalmology journals with higher bibliometric measures of impact tend to publish peer-reviewed articles faster than journals with lower impact scores. Study design of an article may affect its speed to publication.
Keywords: publication speed; ophthalmology; bibliometric; journal impact factor; Eigenfactor score; CiteScore